1995
DOI: 10.1021/ma00124a019
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition in swollen gels. 21. Effect of acrylamide quaternary salts with various alkyl lengths on the collapse, mechanical, and SAXS behavior of poly(acrylamide) networks

Abstract: A series of ionic networks were prepared by copolymerization of acrylamide, methylenebis-(acrylamide), and A/-[2-(alkyldimethylammonio)ethyl]acrylamide with Cl, C4, C6, C8, C12, and C16 straight-chain alkyls (mole fraction of the last comonomer xi = 0-0.15). Small-angle X-ray scattering, swelling, and mechanical behavior of the networks were investigated in water-ethanol mixtures. For the gels with C1-C8 alkyls collapse was found; both the volume jump and the critical ethanol concentration at which the transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…Usually 10 values of λ and f were determined. The shear modulus G was determined from the equation [7,8] where S 0 is the initial cross-section of the specimen. Swelling and mechanical experiments were carried out with samples immediately after preparation at room temperature (modulus G 1 , Table 1) and with the samples swollen to equilibrium in water at various temperatures in the range 15−90 °C or in aqueous NaCl solutions (modulus G) at 23 °C.…”
Section: Swelling and Mechanical Measurementsmentioning
confidence: 60%
See 2 more Smart Citations
“…Usually 10 values of λ and f were determined. The shear modulus G was determined from the equation [7,8] where S 0 is the initial cross-section of the specimen. Swelling and mechanical experiments were carried out with samples immediately after preparation at room temperature (modulus G 1 , Table 1) and with the samples swollen to equilibrium in water at various temperatures in the range 15−90 °C or in aqueous NaCl solutions (modulus G) at 23 °C.…”
Section: Swelling and Mechanical Measurementsmentioning
confidence: 60%
“…As positively charged comonomer (S), (2-acrylamidoethyl)trimethylammonium chloride was used which was synthesized as shown previously [7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ilavsky et al . reported that with increasing length of alkyl chains at a constant mole fraction of hydrophobically modified quarternary salts of acrylamide, the value of the swelling ratio decreased due to the increasing strength of the hydrophobic interactions.…”
Section: Resultsmentioning
confidence: 50%
“…reported that with increasing length of alkyl chains at a constant mole fraction of hydrophobically modified quarternary salts of acrylamide, the value of the swelling ratio decreased due to the increasing strength of the hydrophobic interactions. However, they observed that for the quaternary salt containing C 16 chains the swelling degree is independent of the comonomer mole fraction, and they concluded that the hydrophobic side chains with C 16 alkyl groups could form micelle‐like aggregates in the network . In our study, the Q rv values of S20 and S21 changed slightly with increasing concentration of mCeI (from 5.00 to 10.00 mol %) in the feed, but their swelling degrees were higher than that of the PNIPAAm hydrogels containing C 8 alkyl groups (Table ).…”
Section: Resultsmentioning
confidence: 99%